Mini Symposium ? Mill Design And Grinding Performance Of Large Ball Mills I ? Mill Design - Grinding Performance Of The Ball Mill At The Dizon Operation Of Benguet Corporation - Eduardo M. Sacris (Society for Mining, Metallurgy & Exploration, 1983)
The performance of the grinding circuit, from the initial stages of operation to the present, is discussed. The mill efficiency as measured by the Bond grindability data and the operating work index is presented. The objective has been to produce a sand cyclone overflow containing not more than 6% +65 mesh. However, this has never been attained even at low milling rates. On the other hand, significant improvements in throughput were achieved by instituting some equipment changes and process modifications within the grinding circuit. The latest approach to solving the coarse grind problem is also discussed.